Respuesta :

Answer:

x = -3

Step-by-step explanation:

6(3x-4) + 54 = -3(x+11)

18x-24+54 = -3x-33       Multiply 3x and -4 by 6 this means distributive  

                                          property. Next, multiply x and 11 by -3.

18x+30 = -3x-33            Next, combine -24 and 54 which equals 30.

     -30          -30       Next, subtract 30 from both sides to leave 18x by itself.

18x = -3x-63

+3x   +3x                   Next, add 3x to both sides to leave -63 by itself.

21x = -63

/           /

21       21                 Divide 21 on both sides to leave x by itself.

x = -3